1991
DOI: 10.1159/000195943
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bacteraemic Community-Acquired Lobar Pneumonia due to <i>Streptococcus pneumoniae</i> and <i>Klebsiella pneumoniae</i> in an Intensive Care Unit

Abstract: In a study of 41 consecutive patients with bacteraemia-associated community-acquired lobar pneumonia due to Streptococcus pneumoniae and Klebsiella pneumoniae an attempt was made to determine whether distinguishing criteria of disease due to these organisms could be identified according to demographic features and the results of initial clinical and laboratory investigations. Such information would aid in the early initiation of appropriate antimicrobial therapy. The most significant difference between the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
2

Year Published

1995
1995
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 25 publications
2
24
2
Order By: Relevance
“…This result is consistent with those reported in severe [2-11, 18, 19-23] and nonsevere CAP [12,32,33]. However, the high frequency of isolated K. pneumoniae (22%) is in contrast with the low percentage reported in most published CAP series, with the exception of studies conducted by FELDMAN et al [30,31] in South Africa. The current authors have no hypothesis to explain these similarities, except the location in the south hemisphere region, 2,500 km east of South Africa.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result is consistent with those reported in severe [2-11, 18, 19-23] and nonsevere CAP [12,32,33]. However, the high frequency of isolated K. pneumoniae (22%) is in contrast with the low percentage reported in most published CAP series, with the exception of studies conducted by FELDMAN et al [30,31] in South Africa. The current authors have no hypothesis to explain these similarities, except the location in the south hemisphere region, 2,500 km east of South Africa.…”
Section: Discussionsupporting
confidence: 90%
“…Alcohol abuse was the only RF correlated with death, but was also found to be more frequent in K. pneumoniae CAP compared with other CAPs (table 6). In the literature, alcoholism is generally associated with severe CAP and, particularly, with K. pneumoniae CAP [30,31]. However, the current authors found about half of patients with alcohol abuse in the non-K. pneumoniae group.…”
Section: Discussioncontrasting
confidence: 62%
“…For example, Sullam et al (33) observed that animals rendered selectively thrombocytopenic (but not neutropenic) have significantly worse infective endocarditis due to a PMPsusceptible strain of viridans group streptococci than animals with normal platelet counts. Human studies have also shown thrombocytopenia to be an independent risk factor for infection in organ transplant patients and other patient populations (5,12,35). To our knowledge, no prospective studies have specifically addressed potential relationships between platelet antagonism and an increased risk of infection due to S. aureus.…”
Section: Fig 4 Effects Of Platelet Surface Adhesin Antagonists On Amentioning
confidence: 99%
“…A comparison of bacteremic community-acquired lobar pneumonia due to S. pneumoniae and Klebsiella pneumoniae in an intensive care unit already showed that thrombocytopenia and leukopenia feature with increased frequency in patients with pulmonary infection due to K. pneumoniae (9). However, the pathogenesis of lung injury induced by bacteremia in leukopenic patients after exposure to either microorganism has been poorly defined.…”
mentioning
confidence: 99%